Proceedings of the 8th Working Conference on Mining Software Repositories 2011
DOI: 10.1145/1985441.1985466
|View full text |Cite
|
Sign up to set email alerts
|

Automated topic naming to support cross-project analysis of software maintenance activities

Abstract: Researchers have employed a variety of techniques to extract underlying topics that relate to software development artifacts. Typically, these techniques use semi-unsupervised machine-learning algorithms to suggest candidate word-lists. However, word-lists are difficult to interpret in the absence of meaningful summary labels. Current topic modeling techniques assume manual labelling and do not use domainspecific knowledge to improve, contextualize, or describe results for the developers. We propose a solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 18 publications
2
91
1
3
Order By: Relevance
“…Hindle et al [32], for instance, explored the way NFRs changed over time and examined the difference in emphasis for such issues in MySQL and MaxDB systems. They found that NFRs issues decreased as the systems matured, and interests in such issues for these two systems were driven largely by external technology forces (e.g., the release of new software that needed integration into these products).…”
Section: Android Osmentioning
confidence: 99%
See 2 more Smart Citations
“…Hindle et al [32], for instance, explored the way NFRs changed over time and examined the difference in emphasis for such issues in MySQL and MaxDB systems. They found that NFRs issues decreased as the systems matured, and interests in such issues for these two systems were driven largely by external technology forces (e.g., the release of new software that needed integration into these products).…”
Section: Android Osmentioning
confidence: 99%
“…Alipour et al [42] also included NFRs words to aid with the detection of duplicate bugs. Hindle et al's [32] study, while being somewhat similar to the work that is undertaken here, only examined one version of each of two systems, and was aimed mostly at demonstrating how automated topic extraction techniques are relevant to understanding pass events in software projects. In our context we aim to understand how the Android stakeholders' quality-related concerns shifted over time:…”
Section: Android Osmentioning
confidence: 99%
See 1 more Smart Citation
“…Hindle et al proposed a technique to automatically extract labeled topic to help software maintenance activity in the form of supervised and semi-unsupervised approach [100]. They used only commit comments and not functional requirements but NFR (nonfunctional requirements) are targeted.…”
Section: To Support Development and Managementmentioning
confidence: 99%
“…Additionally, some topics recur over the life of a project. The authors later demonstrated [17] how many of these topics can be named using an automated approach.…”
mentioning
confidence: 99%